Mechanical tolerance stackup and analysis - Fischer, Bryan R., 1960- (Boca Raton : CRC Press, 2011)
"Written by one of the foremost authorities in the field, Mechanical Tolerance Stackup and Analysis presents proven and easy-to-use methods for determining whether selected dimensioning and tolerancing schemes will yield functional parts and assemblies and the most practical procedure to communicate the results. Using a variety of examples and real-world design challenges that stress the importance of a standardized approach to tolerance stackups, the book helps readers develop effective problem-solving and analytical skills. Demonstrates how to perform "what-if" scenarios to evaluate the effects of changing tolerancing schemes, tolerance values, and assembly sequences. Mechanical Tolerance Stackup and Analysis is an outstanding and must-have reference for all mechanical, manufacturing, design, quality control, project, process, industrial, automation, and assembly engineers and managers; and upper-level undergraduate, graduate, and continuing-education students in these disciplines"--
"Written by one of the foremost authorities in the field, this reference presents proven and easy-to-use methods for determining whether selected dimensioning and tolerancing schemes will yield functional parts and assemblies. The book develops effective problem-solving and analytical skills using a variety of examples and real-world design challenges that stress the importance of a standardized approach to tolerance stackups. Illustrating procedures that have been tested and utilized by leading professionals in the industry, this reference demonstrates how to perform "what-if" scenarios to evaluate the effects of changing tolerancing schemes, tolerance values, and assembly sequences"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Tolerance (Engineering); Electronic books